A Major QTL Located in Chromosome 8 of Cucurbita moschata Is Responsible for Resistance to Tomato Leaf Curl New Delhi Virus - Sáez, Cristina; Martínez, Cecilia; Montero-Pau, Javier; Esteras, Cristina; Sifres, Alicia; Blanca, José; Ferriol, María; López, Carmelo; Picó, Belén (Frontiers in Plant Science, 2020)
Tomato leaf curl New Delhi virus (ToLCNDV) is a bipartite whitefly-transmitted begomovirus, responsible since 2013 of severe damages in cucurbit crops in Southeastern Spain. Zucchini (Cucurbita pepo) is the most affected species, but melon (Cucumis melo) and cucumber (Cucumis sativus) are also highly damaged by the infection. The virus has spread across Mediterranean basin and European countries and integrated control measures are not being enough to reduce economic losses. The identification of resistance genes is required to develop resistant cultivars. In this assay, we studied the inheritance of the resistance to ToLCNDV previously identified in two C. moschata accessions. We generated segregating populations crossing both resistant pumpkins, an American improved cultivar Large Cheese (PI 604506) and an Indian landrace (PI 381814), with a susceptible C. moschata genotype (PI 419083). The analysis of symptoms and viral titers of all populations established the same monogenic recessive genetic control in both resistant accessions, and the allelism tests suggest the occurrence of alleles of the same locus. By genotyping with a SNPs collection evenly distributed along the C. moschata genome, a major QTL was identified in chromosome 8 controlling resistance to ToLCNDV. This major QTL was also confirmed in the interspecific C. moschata x C. pepo segregating populations, although C. pepo genetic background affected the resistance level. Molecular markers here identified, linked to the ToLCNDV resistance locus, are highly valuable for zucchini breeding programs, allowing the selection of improved commercial materials. The duplication of the candidate region within the C. moschata genome was studied, and genes with paralogs or single copy genes were identified. Its synteny with the region of chromosome 17 of the susceptible C. pepo revealed an INDEL including interesting candidate genes. The chromosome 8 candidate region of C. moschata was also syntenic to the region in chromosome 11 of melon, previously described as responsible of ToLCNDV resistance. Common genes in the candidate regions of both cucurbits, with high or moderate impact polymorphic SNPs between resistant and susceptible C. moschata accessions, are interesting to study the mechanisms involved in this recessive resistance.